Implementation of the Triple Bottom Line Concept in Business Development for Batik Craftsmen - Nikmah, Farika; Hasan, Halid; Pribadi, Joni Dwi (Budapest International Research and Critics University, 2024)
Triple Bottom Line (TBL) is a concept that is being promoted to be applied to businesses. TBL prioritizes the balance of people, planet and profit in business. No exception for batik craftsmen. Batik crafts in their production process involve a coloring process, which is dangerous for the health of their employees and a washing process that risks disrupting soil fertility. This is the background to this research, so it was carried out at Batik Bambu Kenanga craftsmen, Malang Regency, East Java, Indonesia. The research was carried out using a qualitative approach, with data obtained from observations and interviews. The results of the study found that Batik Bambu Kenanga is run with simple management, although not written and recorded every procedure and business process, Batik Bambu Kenanga has implemented TBL. Such as maintaining the health and safety of its employees when producing batik (implementing people), implementing adequate waste management (implementing planet), and establishing good relationships with village officials, local governments and other parties that influence its production process. These results show that Batik Bambu Kenanga, which has implemented TBL, finally gets convenience in running its business which is correlated with profit achievement. The existence of employee support, support from local residents and support from the government. All of that can guarantee the sustainability of the Batik Bambu Kenanga business and to gain competitive advantage in the midst of batik craft competition.